KOMPOSISI DAN STRUKTUR PERMUDAAN POHON PIONIR BERDASARKAN JENIS TANAH DI KABUPATEN SIAK. - Edmond Edwar; Rasoel Hamidy; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2011)
The results showed that the soil type Latosol consist of 49 species, dominance of the highesttype for Forest Seedlings were Manggis Hutan (Garcinia parvifolia), saplings of Ludai(Sapium beccatum), poles of Mahang (Macaranga gigantea), tree of Sendok-Sendok(Endospermum javanicum). Soil type of Brown Forest Soil consist of 28 species, The highestdominance Seedlings type of Pulai Sudu (Kibatalia boornensis), saplings of Tempinis (Sloetiaelongata), pole of Terap (Artocarpus elasticus), tree of Mahang (Macaranga gigantea). Soiltypes of Organosol consist of 21 species, the highest level of dominance type seedlings KelatMerah (Sizygium cuminii), Kelat Putih (Sizygium subglauca), Kopi-Kopi (Randiaanisophylla), the saplings of Tenggek Burung (Evodia aromatica), the pole of TenggekBurung (Evodia aromatica), The tree of Mahang (Macaranga hypoleuca). The highestspecies dominance values index (1) at the level of tree on the soil type of Organosol andLatosol, while the lowest (0.0426) at the level of sapling on the soil type of Latosol. Thehighest of diversity value index (3.4837) at the level of saplings on the soil type of Latosol,while the lowest (0.0000) at the level of trees on the soil type of Organosol and Latosol. Thehighest of Similarity index (23.33) at the similarity between Brown Forest Soil and Latosol atthe level of saplings, while the lowest of similarity index (0.00) at the similarity betweenLatosol and Brown Forest Soil at the level of tree, Organosol and Latosol at the level ofpoles and tree, Brown Forest Soil and Organosol at the level of seedling, pole and tree.